Butterflies (Lepidoptera: Papilionoidea) of Arequipa, Peru: A checklist, with two new records from Peru - Farfán Larico, Jackie (2018)
A list of 74 butterfly species recorded until present at the Arequipa Department, Peru, is presented herein. Two new records from Peru of Strymon flavaria (Ureta 1956) and Hylephila herrerai MacNeill 2002 are reported herein, both described from northern Chile. Comments for species cited to Arequipa in the literature and that were excluded from this preliminary list are provided.